Critical Thinking Integration in Writing Development - Patty, Jusak (Huele: Journal of Applied Linguistics, Literature and Culture, 2024)
This study investigates the integration of critical thinking in writing education through library research design, focusing on the relationship between critical thinking strategies and writing quality enhancement. The research examines four key dimensions: the impact of critical thinking instruction on writing development, the challenges and opportunities in digital writing environments, the complexities of assessing critical thinking in writing, and the synergistic relationship between critical thinking and creativity. The findings reveal that specific critical thinking strategies—particularly argumentation, analysis, and synthesis—significantly enhance students' writing capabilities across educational levels. Digital writing environments, while presenting challenges in information evaluation and ethical considerations, offer valuable opportunities for collaborative learning and immediate feedback. The study also identifies limitations in traditional assessment methods, highlighting the need for alternative approaches such as portfolio-based evaluations and detailed rubrics. Furthermore, the research emphasizes the fundamental connection between critical and creative thinking processes in writing development, demonstrating how their integration fosters analytical rigor and innovative expression. These findings contribute to understanding effective writing instruction in contemporary educational contexts and provide insights for educators developing comprehensive writing programs incorporating critical thinking development.